Lightweight vibration and noise reduction structure bonding adhesive and preparation method thereof
By adding high-dampening materials and rubber components to the structural adhesives, the formulation is optimized and the curing temperature is reduced, and the shortcomings of existing adhesives in vibration reduction, noise reduction, adhesive strength and curing temperature are solved, achieving efficient, energy-saving and multifunctional adhesive effects.
Patent Information
- Application Number
- CN202510132343.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-04-08
AI Technical Summary
The existing structural adhesive lacks vibration and noise reduction function, the existing damping adhesive cannot provide strong adhesive force, and the high curing temperature leads to waste of energy and poor applicability.
Epoxy resin is used as the matrix, combining high-damping materials and rubber components, optimize the adhesive formula, enhance cohesion and toughness, reduce curing temperature, and select high temperature resistance and ultraviolet resistant resin and filler combinations.
It has achieved excellent vibration and noise reduction functions, strong structural bonding capabilities, low-temperature curing, environmental adaptability and energy-saving effects, and comprehensively improved the performance and applicability of the adhesive.
Smart Images

Figure CN119775939A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a lightweight vibration-damping and noise-reducing structural bonding adhesive and a preparation method thereof. Background Art
[0002] As the demand for structural adhesives in the fields of automobiles, construction, and electronic equipment continues to increase, existing structural adhesives and damping adhesives have gradually shown some shortcomings in many applications, especially in terms of vibration reduction and noise reduction, structural bonding performance, and low-temperature curing. Although the prior art provides various types of adhesives, there are still many technical gaps and room for improvement, which provides an innovative opportunity for the present invention.
[0003] First of all, existing structural adhesives usually focus on providing strong structural bonding performance, and are mainly used to bear the bonding needs of various objects. The common matrix of structural adhesives is epoxy resin. This type of adhesive can provide high strength and durability, and is widely used in industries such as automobiles and construction. However, the disadvantage of this type of adhesive is that it lacks vibration reduction and noise reduction functions. Most of the existing structural adhesives only focus on bonding performance and fail to effectively combine the needs of vibration reduction and noise reduction. In practical applications, due to the inherent rigidity and bonding method of structural adhesives, they often cannot fully suppress the noise and vibration generated by vehicle driving or building vibration. Due to the increasingly stringent requirements of modern vehicles and buildings on noise and vibration, existing technologies are obviously unable to meet the growing vibration reduction and noise reduction needs of these industries.
[0004] Secondly, although existing damping adhesives can effectively provide vibration and noise reduction functions, they are often applied to car bodies, buildings and electronic equipment through paving to reduce vibration and noise. However, the lack of structural bonding ability of existing damping adhesives makes them only suitable for additional applications and cannot undertake the task of load-bearing bonding. This type of damping adhesive can often only contact the bonded object through direct bonding, and cannot provide a stable and lasting bonding effect between structural parts, which limits their application in high-strength bonding environments. Especially in the fields of car bodies, aircraft, building structures, etc., the dual needs of bonding and vibration and noise reduction are becoming more and more prominent, and a single damping adhesive cannot meet this demand.
[0005] Furthermore, the curing temperature issue is also a significant challenge faced by existing adhesives. Many traditional epoxy resin-based adhesives, such as existing structural adhesives and damping adhesives, require higher curing temperatures to obtain adequate performance. These adhesives usually need to reach temperatures of 150°C and above for curing, which not only consumes a lot of energy, but also limits the application of some heat-sensitive materials. Therefore, in some temperature-sensitive material applications, existing adhesives are not applicable, resulting in problems with curing efficiency and energy waste.
[0006] Therefore, the present invention proposes a lightweight vibration and noise reduction structural bonding adhesive and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a lightweight vibration-damping and noise-reducing structural bonding adhesive and a preparation method thereof, which solves the problems that the existing structural adhesives lack vibration-damping and noise-reducing functions, and the existing damping adhesives cannot provide strong bonding force and high curing temperature, resulting in energy waste and poor applicability.
[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions: A lightweight vibration and noise reduction structural bonding adhesive, comprising the following raw material components in parts by mass: Bisphenol A epoxy resin: 10% to 30%; Bisphenol F epoxy resin: 5% to 20%; Polyphenol type glycidyl ether epoxy resin: 5% to 20%; Polyurethane resin: 5% to 15%; CTBN modified epoxy resin: 5%~15%; Dimer acid modified epoxy resin: 5% to 15%; Filler: 30%~50%; Curing agent: 2%~10%; Accelerator: 1%~5%; Diluent: 2%~8%; Thixotropic agent: 1%~5%.
[0009] Preferably, the filler includes one or more of calcium carbonate, calcium oxide, wollastonite, mica powder, carbon black, and barite.
[0010] Preferably, the curing agent includes one or more of dicyandiamide, imidazole curing agent and acid anhydride curing agent.
[0011] Preferably, the dicyandiamide curing agent is dicyanovinyl dicyandiamide, the imidazole curing agent is 1-methylimidazole; and the anhydride curing agent includes one or more of phthalic anhydride and tetrafluorophthalic anhydride.
[0012] Preferably, the diluent includes one or more of active diluents and inactive diluents; the active diluent includes epoxy compound diluents and phenyl glycidyl ether, and the inactive diluent includes one or more of aromatic hydrocarbon solvents and ester solvents.
[0013] Preferably, the thixotropic agent includes one or more of fumed silica and organic bentonite.
[0014] Preferably, a method for preparing a lightweight vibration-damping and noise-reducing structural bonding adhesive comprises the following steps: S1: adding bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, polyurethane resin and selected diluent into a mixer, and starting to stir until uniform, wherein the diluent is an active diluent or an inactive diluent, and the mass ratio of the resin to the diluent is 1:0.1 to 1:0.5; S2: Add filler to the resin mixture obtained in S1 and continue stirring for 10 to 30 minutes; S3: Add curing agent and accelerator and continue stirring; S4: Add thixotropic agent and continue stirring to ensure that the thixotropic agent is fully dispersed. The stirring time is 5 to 15 minutes; S5: vacuuming the mixture at a vacuum pressure of -0.100 MPa for 5 to 15 minutes to remove bubbles in the adhesive; S6: Extrude and fill the obtained adhesive for standby use.
[0015] Preferably, the mixer is a double planetary mixer, and the stirring speed of the mixer is 30 to 60 rpm, and the temperature is controlled not to exceed 80° C. during the stirring process.
[0016] Preferably, the amount of the curing agent added is 2% to 10% of the total mass of the adhesive, and the temperature when the curing agent is added is controlled at 20° C. to 40° C. to ensure uniform curing reaction.
[0017] The present invention provides a lightweight vibration-reducing and noise-reducing structural bonding adhesive and a preparation method thereof. It has the following beneficial effects: 1. The present invention uses epoxy resin as the matrix, supplemented with high damping materials and rubber components, and optimizes the adhesive formula to enable it to have excellent vibration reduction and noise reduction functions. By enhancing the cohesion and toughness of the adhesive, vibrations can be effectively absorbed and noise can be suppressed. This technological innovation solves the defect that existing structural adhesives only have structural bonding effects and cannot achieve vibration reduction and noise reduction. Compared with traditional damping materials that only rely on paving, the present invention can not only provide an effective vibration reduction effect, but also has a strong structural bonding ability, which comprehensively improves the comfort and performance of the usage scenario.
[0018] 2. By optimizing the curing system, the present invention uses a curing agent and an accelerator with high reactivity and good storage stability, which effectively reduces the curing temperature. This technical solution solves the problem that the existing structural adhesive requires a higher curing temperature, reduces energy consumption and improves production efficiency. The high-temperature curing in the prior art not only consumes a lot of energy, but also limits the applicability of the adhesive to heat-sensitive materials. The low-temperature curing characteristics of the present invention ensure that it can be used in a wider range of application fields, with better energy-saving effects and environmental advantages.
[0019] 3. The present invention significantly enhances the bonding strength of the adhesive by accurately selecting and blending the types and proportions of fillers, ensuring stability when subjected to tensile and shear forces. This innovative technology solves the problem that existing damping adhesives only have a damping function but cannot provide sufficient bonding strength. In contrast, the present invention not only has a damping and vibration reduction effect, but also can meet the strong bonding requirements in industrial requirements, solving the problem that traditional damping adhesives cannot be used in structural bonding, and making it show better comprehensive performance in practical applications.
[0020] 4. The adhesive of the present invention takes into account the changing environmental factors when designing, and adopts a combination of high temperature-resistant and UV-resistant resins and fillers, so that it can still maintain stable performance in harsh environments such as hot and humid, alternating hot and cold, and UV irradiation. In the prior art, many adhesives are prone to failure or aging in harsh environments, while the technology of the present invention enhances the environmental adaptability of the adhesive, ensures its stability and durability in long-term use, thereby extending its service life and reducing maintenance frequency and replacement costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Flow chart of the preparation method of lightweight vibration and noise reduction structural bonding adhesive. DETAILED DESCRIPTION
[0022] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Please see attached Figure 1 : Embodiment 1: The present invention provides a damping structural adhesive that can be cured at low temperature and has vibration and noise reduction functions. The raw materials are measured by weight, and 3 parts of bisphenol A epoxy resin, 18 parts of dimer acid modified epoxy resin, 27.5 parts of CTBN modified epoxy resin, 12 parts of polyurethane, and 3 parts of active diluent are added to a double planetary mixer, and stirred at 50rpm for 30min, and 1 part of carbon black, 8 parts of calcium carbonate, 2 parts of calcium oxide, 2 parts of wollastonite, and 17 parts of barite are added in sequence, and stirred at 35rpm for 6min, 1.9 parts of dicyandiamide curing agent and 1.2 parts of substituted urea accelerator are added, and stirred at 30rpm for 6min, 0.7 parts of organic bentonite and 0.8 parts of fumed silica are added, and stirred at 30rpm for 20min, and vacuum is set to a vacuum pressure of -0.100MPa, and stirred at 30rpm for 20min to obtain the damping structural adhesive, which is extruded and filled.
[0024] Embodiment 2: The present invention provides a damping structural adhesive that can be cured at low temperature and has vibration and noise reduction functions. The raw materials are calculated by weight, and 3 parts of bisphenol A epoxy resin, 18 parts of polyacrylate, 27.5 parts of CTBN modified epoxy resin, 12 parts of liquid butyl rubber, and 3 parts of active diluent are added to a double planetary mixer, and stirred at 50rpm for 30min, and 1 part of carbon black, 8 parts of calcium carbonate, 2 parts of calcium oxide, 2 parts of wollastonite, and 17 parts of barite are added in sequence, and stirred at 35rpm for 6min, and 1.9 parts of dicyandiamide curing agent and 1.2 parts of imidazole accelerator are added, and stirred at 30rpm for 6min, and 0.7 parts of organic bentonite and 0.8 parts of fumed silica are added, and stirred at 30rpm for 20min, and vacuum is set to a vacuum pressure of -0.100MPa, and stirred at 30rpm for 20min to obtain the damping structural adhesive, which is extruded and filled.
[0025] Embodiment 3: The present invention provides a damping structural adhesive that can be cured at low temperature and has vibration and noise reduction functions. The raw materials are measured by weight, and 5 parts of bisphenol F epoxy resin, 18 parts of dimer acid modified epoxy resin, 27.5 parts of CTBN modified epoxy resin, 12 parts of silicone resin, and 3 parts of active diluent are added to a double planetary mixer, and stirred at 50rpm for 30min, and 1 part of carbon black, 8 parts of calcium carbonate, 2 parts of calcium oxide, 2 parts of wollastonite, and 17 parts of barite are added in sequence, and stirred at 35rpm for 6min, and 1.9 parts of anhydride curing agent and 1.2 parts of imidazole accelerator are added, and stirred at 30rpm for 6min, and 0.7 parts of organic bentonite and 0.8 parts of polyamide wax are added, and stirred at 30rpm for 20min, and vacuum is set to a vacuum pressure of -0.100MPa, and stirred at 30rpm for 20min to obtain the damping structural adhesive, which is extruded and filled.
[0026] Comparative Example 1: Raw material composition: Bisphenol A epoxy resin: 20% Polyester resin: 20% Filler (such as calcium carbonate, wollastonite): 40% Curing agent (such as dicyandiamide): 10% Accelerator (such as imidazole): 5% Diluent: 5% Preparation steps: Add bisphenol A epoxy resin, polyester resin and diluent into a double planetary mixer and stir until uniform.
[0027] Add filler and continue stirring for 5 to 10 minutes to ensure that the filler is evenly dispersed.
[0028] Add curing agent and accelerator and continue stirring to ensure thorough mixing.
[0029] The mixture was put into a mold, the curing temperature was 150°C, and the curing time was 30 minutes.
[0030] Comparative Example 2: Raw material composition: Polyurethane resin: 25% Polyacrylate: 20% Polyester rubber: 20% Calcium carbonate: 20% Calcium oxide: 5% Curing agent (such as imidazole): 5% Thixotropic agent (such as fumed silica): 5% Preparation steps: Mix the polyurethane resin, polyacrylate and diluent and stir in a mixer for 10 to 15 minutes.
[0031] Add fillers (calcium carbonate, calcium oxide) and thixotropic agent and continue stirring for 10 minutes to ensure uniform dispersion.
[0032] Add curing agent and continue stirring until the viscosity of the adhesive meets the requirements.
[0033] The mixture was heated to 100°C for curing.
[0034] Comparative Example 3: Raw material composition: Bisphenol A epoxy resin: 3% Polyurethane resin: 12% Polyester resin: 18% CTBN modified epoxy resin: 27.5% Active diluent: 3% Carbon black: 1% Calcium carbonate: 8% Calcium oxide: 2% Wollastonite: 2% Barite: 17% Dicyandiamide curing agent: 1.9% Substituted urea accelerator: 1.2% Organic bentonite: 0.7% Fumed silica: 0.8% Preparation steps: Add bisphenol A epoxy resin, polyurethane resin, polyester resin and reactive diluent into a double planetary mixer and stir until uniform.
[0035] Add fillers (such as carbon black, calcium carbonate, etc.) and other fillers, and stir for 10 to 20 minutes to ensure thorough mixing.
[0036] Add dicyandiamide curing agent and substituted urea accelerator and continue stirring.
[0037] Add thixotropic agents such as organobentonite and fumed silica and continue stirring for 30 minutes.
[0038] The mixture was evacuated to -0.100 MPa and stirring was continued for 20 minutes.
[0039] Extrusion and filling of the final mixture Test experiment: Purpose: This experiment aims to verify the advantages of the damping structural adhesive of the present invention, which cures at low temperature and has vibration and noise reduction functions, over the prior art in multiple key aspects, including vibration and noise reduction, structural bonding strength, low temperature curing ability, construction performance and durability, etc. Through comprehensive testing, the innovation of the present invention is demonstrated, and its applicability in practical applications in various industrial fields is proved.
[0040] Experimental Materials: Sample 1 (the present invention): The damping structural adhesive of the present invention which cures at low temperature and has vibration reduction and noise reduction functions is prepared according to the formula in the claims, based on epoxy resin as the matrix, and reinforced materials such as high damping resin, rubber and filler are added.
[0041] Sample 2 (existing structural adhesive): A high-curing temperature structural adhesive commonly used in the market, usually used for bonding automotive or building components. It does not have vibration reduction and noise reduction functions, and mainly provides structural stability through high-strength bonding.
[0042] Sample 3 (existing damping glue): Common damping glue on the market, which mainly achieves vibration reduction and noise reduction effects through paving, but does not have structural bonding properties and cannot be used for structural bonding.
[0043] Sample 4 (damping glue with fine-tuned formula): The damping glue with fine-tuned formula in the comparison experiment has a certain vibration reduction effect, but does not have low-temperature curing and strong adhesion.
[0044] equipment: Universal testing machine: used for tensile and shear tests to measure the bond strength of adhesives under stress.
[0045] Vibration table: used to test the vibration reduction effect and simulate vibrations of different frequencies and intensities.
[0046] Noise sensor: Measures the noise reduction caused by the vibration reduction effect.
[0047] Curing oven: used to test the curing temperature and curing time to ensure the curing conditions of different samples.
[0048] Environmental simulation device: used to simulate changes in temperature and humidity and test the durability of adhesives under various environmental conditions.
[0049] UV aging tester: used to simulate long-term ultraviolet radiation to test the aging of adhesives.
[0050] Experimental steps and details: Vibration reduction performance test Experimental purpose: To verify the effect of the damping structural adhesive of the present invention in reducing vibration and noise, and to compare the performance of different adhesives through vibration transmission and noise tests.
[0051] Experimental materials: Prepare each set of adhesive (100g per set) according to the test standard and apply it on the metal panel to ensure that the coating thickness is uniform.
[0052] Experimental steps: Sample 1, sample 2, sample 3, and sample 4 were coated on four metal panels of the same size, with an area of about 100 cm 2 , the coating thickness is 1mm.
[0053] Mount each panel on the shaker table, ensuring that the adhesive layer is in close contact with the shaker table surface.
[0054] Set the vibration frequency range to 20-200Hz and the amplitude to 10mm, and start the vibration test.
[0055] The vibration transmission efficiency of the panel was measured using a triaxial vibration sensor, and the noise intensity generated by the vibration was recorded using a noise sensor.
[0056] The vibration intensity and frequency were adjusted step by step, and the vibration transmission reduction rate (%) and noise reduction (dB) of each sample were recorded.
[0057] Technical details: The vibration damping performance of each adhesive is measured by changing the frequency range of the vibration table. The comparative experiment will verify the improvement of the present invention in vibration suppression through this parameter.
[0058] Vibration transmission reduction rate: The calculation formula is: (vibration intensity of the sample without glue - vibration intensity of the sample with glue) / vibration intensity of the sample without glue × 100%. Ideally, the reduction rate should be greater than 20%.
[0059] Noise reduction value: The noise reduction at different frequencies is directly measured by the noise sensor, in dB.
[0060] Structural bond strength testing Purpose of the experiment: To evaluate the structural bonding capabilities of each adhesive, including tensile strength and shear strength.
[0061] Experimental materials: Each set of adhesive was applied between two metal plates with a bonding area of 50 cm² and a coating thickness of 1 mm.
[0062] Experimental steps: Align the metal panels, apply the required adhesive, and secure with a clamp to ensure an even coating without bubbles.
[0063] At room temperature, perform a tensile test: fix the metal plate on a universal testing machine with a tensile fixture, and gradually increase the tensile force until the adhesive fails or is damaged.
[0064] To perform a shear test, place the metal panel in a shear fixture and apply shear force until the adhesive fails.
[0065] Record the maximum tensile strength (N / mm 2 ) and shear strength (N / mm 2 ).
[0066] Technical details: The tensile test and shear test were carried out using standard experimental procedures, with a tensile speed of 5 mm / min and a shear speed of 2 mm / min.
[0067] Each sample was tested at least 3 times, and the average value was taken as the final result.
[0068] The adhesive of the present invention should demonstrate higher structural bonding strength than existing damping adhesives and structural adhesives, especially the strength in tensile and shear tests.
[0069] Curing temperature and curing time test Experimental purpose: To verify the advantages of the adhesive of the present invention under low temperature curing, and to ensure stable curing at a lower temperature compared with the prior art.
[0070] Experimental materials: Each set of adhesive is coated on a metal sheet with a thickness of 1 mm and the number of samples is 5.
[0071] Experimental steps: Each adhesive sample was coated on a fixed metal sheet to ensure uniform thickness.
[0072] The samples were placed in a curing oven and set at different temperatures such as 130°C, 150°C, and 170°C for curing tests.
[0073] Record the curing time (minutes) for each sample until the adhesive is fully cured and reaches the desired hardness.
[0074] The final hardness of each sample was measured and its post-curing performance was evaluated using a durometer.
[0075] Technical details: The curing temperature and curing time are controlled by adjusting the curing oven temperature and timer.
[0076] Curing time is the moment when the hardness of the sample reaches the appropriate standard, recorded and compared with the existing technology.
[0077] Ideally, the sample of the present invention is cured at 130°C and has a short curing time, which shows obvious advantages compared to the existing structural adhesive that is cured at 150°C.
[0078] Comprehensive performance evaluation Experimental purpose: Through simulated environmental testing, comprehensively evaluate the adaptability, durability and construction performance of the adhesive.
[0079] Experimental materials: Each set of adhesives was applied to metal structural parts to simulate car bodies or building structures.
[0080] Experimental steps: Apply each set of adhesive to the surface of the structural component and ensure that the coating is even.
[0081] The samples were exposed to different temperature and humidity environments (temperature: -20°C to 60°C, humidity: 20%-90%) for environmental adaptability tests.
[0082] The samples were subjected to long-term vibration tests using a mechanical vibration simulation table and their stability was recorded.
[0083] Use a UV aging tester to simulate long-term UV exposure and record the aging of the adhesive.
[0084] By alternating hot and cold, the high and low temperature changes in the actual environment are simulated, and the changes in adhesion are recorded.
[0085] The environmental adaptability experiment needs to be carried out for 1 month, and the decline of adhesion strength should be recorded every week.
[0086] The durability test simulates the effects of long-term vibration and aging, using a vibration simulation table set to a frequency of 10-100Hz to simulate the vibration conditions during use.
[0087] Experimental data: The above experimental tests demonstrate the innovation and technical advantages of the damping structural adhesive of the present invention, which cures at low temperature and has vibration and noise reduction functions. First, in terms of vibration reduction performance, the vibration transmission reduction rate and noise reduction effect of the adhesive of the present invention are significantly better than those of existing structural adhesives and damping adhesives, proving its uniqueness in vibration and noise reduction. This effect is due to the careful proportion of fillers and resins, especially the addition of high damping materials, which enhances the adhesive's ability to suppress vibration and noise.
[0088] Secondly, the test results of the structural bonding strength in the experiment show that the tensile strength and shear strength of the adhesive of the present invention are significantly higher than those of the existing damping adhesive and structural adhesive, which fully verifies its innovation in bonding ability. Through the adjustment of specific resin and curing agent formula, the present invention not only meets the vibration reduction requirements, but also provides sufficient structural bonding strength, solving the problem of the lack of bonding strength of damping materials in the prior art.
[0089] In addition, the adhesive of the present invention has significant advantages in terms of curing temperature and curing time. Under low-temperature curing at 130°C, the adhesive can be effectively cured and maintain a short curing time, saving energy and reducing production costs. This performance is particularly suitable for applications in the automotive, construction and other industries, which can reduce energy consumption and improve production efficiency.
[0090] Comprehensive performance tests show that the adhesive of the present invention not only has excellent vibration reduction and noise reduction and bonding performance, but also can maintain stability under harsh environmental conditions. Its performance under wet and hot, hot and cold alternation and ultraviolet irradiation is better than the existing technology, demonstrating its broad application prospects.
[0091] Overall, the low-temperature curing damping structural adhesive of the present invention successfully solves many problems in the prior art by virtue of its advantages in vibration reduction and noise reduction, strong bonding, low-temperature curing and comprehensive performance. By optimizing the formula and process, the present invention provides an efficient, energy-saving and multifunctional adhesive solution with wide market application value.
[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A lightweight vibration and noise reduction structural bonding adhesive, characterized in that: The raw material components include the following parts by weight: Bisphenol A epoxy resin: 10% to 30%; Bisphenol F epoxy resin: 5% to 20%; Polyphenol type glycidyl ether epoxy resin: 5% to 20%; Polyurethane resin: 5% to 15%; CTBN modified epoxy resin: 5%~15%; Dimer acid modified epoxy resin: 5% to 15%; Filler: 30%~50%; Curing agent: 2%~10%; Accelerator: 1%~5%; Diluent: 2%~8%; Thixotropic agent: 1%~5%.
2. A lightweight vibration and noise reduction structural bonding adhesive according to claim 1, characterized in that: The filler includes one or more of calcium carbonate, calcium oxide, wollastonite, mica powder, carbon black, and barite.
3. A lightweight vibration and noise reduction structural bonding adhesive according to claim 1, characterized in that: The curing agent includes one or more of dicyandiamide, imidazole curing agent and acid anhydride curing agent.
4. A lightweight vibration and noise reduction structural bonding adhesive according to claim 3, characterized in that: The dicyandiamide curing agent is dicyanovinyl dicyandiamide, the imidazole curing agent is 1-methylimidazole; the anhydride curing agent includes one or more of phthalic anhydride and tetrafluorophthalic anhydride.
5. The lightweight vibration and noise reduction structural bonding adhesive according to claim 1, characterized in that: The diluent includes one or more of active diluents and inactive diluents; the active diluent includes epoxy compound diluents and phenyl glycidyl ether, and the inactive diluent includes one or more of aromatic hydrocarbon solvents and ester solvents.
6. A lightweight vibration and noise reduction structural bonding adhesive according to claim 1, characterized in that: The thixotropic agent includes one or more of fumed silica and organic bentonite.
7. A method for preparing a lightweight vibration and noise reduction structural bonding adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Add bisphenol A epoxy resin, bisphenol F epoxy resin, polyphenol glycidyl ether epoxy resin, polyurethane resin and selected diluent into a mixer and start stirring until uniform; S2: Add filler to the resin mixture obtained in S1 and continue stirring for 10 to 30 minutes; S3: Add curing agent and accelerator and continue stirring; S4: Add thixotropic agent and continue stirring to ensure that the thixotropic agent is fully dispersed. The stirring time is 5 to 15 minutes; S5: vacuuming the mixture at a vacuum pressure of -0.100 MPa for 5 to 15 minutes to remove bubbles in the adhesive; S6: Extrude and fill the obtained adhesive for standby use.
8. The method for preparing a lightweight vibration and noise reduction structural bonding adhesive according to claim 7, characterized in that: The mixer is a double planetary mixer, and the mixing speed of the mixer is 30 to 60 revolutions per minute. During the mixing process, the temperature is controlled not to exceed 80°C.
9. The method for preparing a lightweight vibration and noise reduction structural bonding adhesive according to claim 7, characterized in that: The amount of the curing agent added is 2% to 10% of the total mass of the adhesive, and the temperature when the curing agent is added is controlled at 20° C. to 40° C. to ensure uniform curing reaction.
Citation Information
Cited By
Carbon fiber composite material with high-frequency-band damping performance and preparation method thereof
CN120504936A
Weldable high-damping glue and application thereof
CN122011964A